PDP law and the university data ecosystem: understanding the context - Zulhuda, Sonny (2014)
Educational institutions -universities, colleges, schools, etc.- are among those who are regulated by the Personal Data Protection Act (PDPA) 2010. The data subjects include: students (obviously the main object here), staffs or employees, vendors, alumni, sponsors, as well as those applicants who have yet join the universities/schools. The amount of personal data are potentially bulky: personal details, medical records, financial and scholarship records, academic records, student societies records, disciplinary records and even post-study information about the students. Given this situation, people who deal with students’ data in the educational institutions would need to ensure their handling of personal data is in line with the demands of the Act.